VD_FINDINFO Décision / 2016 / 124 vom 18. Februar 2016 - VD Tribunal cantonal (2016)
CLASSEMENT DE LA PROCÉDURE, FRAIS JUDICIAIRES, INDEMNITÉEN GÉNÉRAL | 319 CPP (CH), 426 al. 2 CPP (CH), 429 CPP (CH)